The Effect of the Implementation of Project Based Learning (PjBL) in Improving the Cognitive Learning Outcomes on the Material of Atomic Structure - Sukmaningsih, Gusti Ayu Diah; Fahyuddin, Fahyuddin; Musta, Rustam (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aimed to analyze students’ cognitive learning outcomes taught using the Project Based Learning (PjBL) model compared to direct instruction, examine the effect of PjBL on improving cognitive learning outcomes on atomic structure material, and describe students’ responses to the PjBL implementation. The research employed a quasi-experimental method with a Control Group Pretest–Posttest design. The subjects were 62 tenth-grade students of SMA Negeri 12 Kendari in the 2025/2026 academic year, consisting of 31 students in the experimental class and 31 students in the control class. The instruments used were a cognitive learning outcomes test and a student response questionnaire. Data were analyzed using inferential statistical tests. The results showed that the experimental class achieved a higher average cognitive score of 82.90 (very good category) compared to the control class, which obtained an average score of 73.23 (good category). The independent sample t-test revealed a significance value of 0.001 (< 0.05), indicating that the PjBL model significantly improved students’ cognitive learning outcomes. Students’ responses toward the PjBL model were also very positive, with an average percentage of 80.13%. These findings indicate that the PjBL model is effective in teaching atomic structure material to enhance students’ cognitive learning outcomes .